2004
DOI: 10.1111/j.1365-2427.2004.01319.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of a beaded Arctic stream to short‐term N and P fertilisation

Abstract: 1. Oligotrophic Arctic streams are likely to be sensitive to changes in hydrology and nutrient inputs predicted to occur as a consequence of future climate and land use change.To investigate the potential consequences of nutrient enrichment for low-order Arctic streams, we added ammonium-N and phosphorous to a second-order beaded, tundra stream on Alaska's north slope. We measured responses in nutrient chemistry, chlorophyll a standing crop, and in the breakdown and macroinvertebrate colonisation of leaf litte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 44 publications
1
32
1
Order By: Relevance
“…We found that nutrient levels were significantly enhanced in spring-fed rivers and probably contributed to increased invertebrate density at these sites. Benstead et al (2005) found that invertebrate abundance was 4 to 7× greater in an oligotrophic stream ecosystem after the addition of N and P and suggested that these changes were a result of enhanced food resources. Perrin and Richardson (1997) found that N and P additions to mesocosms increased mean invertebrate density by 70% over a period of 33 d and attributed their results to an increase in epilithic algal production.…”
Section: Invertebrate Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…We found that nutrient levels were significantly enhanced in spring-fed rivers and probably contributed to increased invertebrate density at these sites. Benstead et al (2005) found that invertebrate abundance was 4 to 7× greater in an oligotrophic stream ecosystem after the addition of N and P and suggested that these changes were a result of enhanced food resources. Perrin and Richardson (1997) found that N and P additions to mesocosms increased mean invertebrate density by 70% over a period of 33 d and attributed their results to an increase in epilithic algal production.…”
Section: Invertebrate Densitymentioning
confidence: 99%
“…Similar correlations between spring-fed invertebrate assemblages and elevated food resources have been reported from both Spain and New Zealand Death 2004, 2006). Nutrient availability and productivity have also been shown to positively affect invertebrate population growth rates and carrying capacity in other stream ecosystems (Slavik et al 2004, Benstead et al 2005.…”
Section: Invertebrate Diversity and Community Compositionmentioning
confidence: 99%
“…These observed increases in biological activity have been linked to changes in uptake rates of N and P in headwater streams that may influence the mass and form of nutrient exports. Few published studies, however, report direct measurements of nutrient uptake rates for Arctic streams, and these have been geographically limited to streams in Alaska (Wollheim et al 2001;Slavik et al 2004;Benstead et al 2005;Greenwald et al 2008). Comparable studies of streams in the Siberian Arctic are notably absent.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in leaf-litter decomposition rates often are attributed to enhanced heterotrophic activity in response to nutrient enrichment. Increases in N and P availability can stimulate microbial biomass (Rosemond et al 2002, Benstead et al 2005, Suberkropp et al 2010) and respiration rates (Elwood et al 1981, Stelzer et al 2003, Suberkropp et al 2010) associated with leaf litter. However, relatively few investigators have demonstrated how increased nutrient availability might affect leaf-litter quality (defined by nutrient content and stoichiometric ratios).…”
mentioning
confidence: 99%